A case study analysis : Tenaga Nasional Berhad / Alice Nurulzila Ab. Aziz … [et al.] - Ab. Aziz, Alice Nurulzila (Faculty of Business and Management, 2001)
The Malaysian Government established Tenaga Nasional Berhad (TNB) in September 1990 through a corporatisation and privatization exercise. The corporatization is regulated under the Electricity Supply Department under the Ministry of Energy, Telecommunications and Posts, Malaysia. The move to transform the former government electricity utility into a private entity was highly successful because of TNB's unique position as a monopoly in the generation, transmission and distribution of electricity in Peninsular Malaysia. Another major contributing factor in its successful business development has been the utility's legacy, one rich in experience and expertise, from its predecessor, the Central Electricity Board (CEB) established in 1949, which in 1965 was renamed the National Electricity Board (NEB), to meet national aspirations.